Arabic to English Translation of Islamic Religious Texts - Chebbo, Ann Ainlay (2006)
A Master of Arts thesis in English/Arabic/English Translation and Interpreting by Ann Ainlay Chebbo Entitled, "Arabic to English Translation of Islamic Religious Texts" April 2006. Thesis Advisor is Dr. Said Faiq. Available are both Soft and Hard Copies of the Thesis.